The legal framework for the acceptance and affirmation of public deals - Krikou, Feriel (Journal of Human Sciences, 2020)
It appears that the new amendment in the area of public deals and public utility delegations has marked a significant paradigm shift,through devoting it to the values of transparency and the promotion of competition mechanisms with other principles of non-discrimination, equality, integrity and methods of appeal as pillars of the state of law and right, in order to achieve a fair investment climate which will not be realized only by the strict application of the laws on all the levels to ensure the efficacy of public demand. As it is not possible to talk about the presence of acceptance and affirmation in the administrative contract unless the public person has contractual freedom that allows him to enter into contractual relations based on the delicate balance between common interest represented by the administration and the other interest represented by the other chambers contracted with the administration. Therefore, the procedural framework for affirmation and acceptance in the administrative contract is based on two fundamental concepts (the deal) and they are: the free competition, which is the basis of economic freedom, and the equivalence between individuals and equal opportunities between them. In addition to the standard of openness, which is the legal way that leads to putting the principle of free competition into practice.